Integration of Values, Culture of Linguistic Politeness and Digital Technology in Educational Development: A Study of Gibran Rakabuming Raka's Twitter Comment Column - Nasution, Habib Syukri; Mahriyuni, Mahriyuni (Jurnal Riset Ilmu Pendidikan, 2025)
The integration of values, culture of politeness, and digital technology in education is key to creating a knowledgeable, cultured, and ethical generation. In the 21st century, one of the national characteristics that is starting to fade is the cultural values of politeness, which are being eroded by the sophistication of science and technology. This paper aims to identify violations of values, culture, and politeness from an educational perspective, specifically character education, in Gibran Rakabuming Raka's Twitter comment column. The method used is netnography, a form of ethnography adapted to the social world mediated by computer devices. Of the 25 netizen comments sampled, there were 9 (22.5%) comments violating the Maxim of Tact, 7 (17.5%) comments violating the Maxim of Praise, 2 (5%) comments violating the Maxim of Sympathy, 3 (7.5%) comments violating the Maxim of Politeness, 2 (5%) comments violating the Maxim of Humility, 1 (2.5%) comment violating the Maxim of Generosity, and 1 (2.5%) comment violating the Maxim of Agreement. Thus, it is concluded that there is a violation of the cultural values of politeness in language committed by netizens in the Twitter comment column of Gibran Rakabuming Raka.